Skeletal traction pin diameter and deflection under load: a biomechanical evaluation with clinical correlation. Issue 5 (September 2019) - Evans, Cody L.; Hadeed, Michael M.; Casp, Aaron J.; Yarboro, Seth R.
Abstract : Background: There is scant literature to guide the placement of skeletal traction. The purpose of this study was to test a tensioned traction bow, a nontensioned traction bow, and a traction set up without a bow to measure the amount of pin deflection. By quantifying the deflection of various traction systems under load, guidelines can be provided regarding equipment selection for skeletal traction. The goal was to develop a protocol to minimize the equipment necessary and time to traction placement. Methods: A Sawbones® skeletal traction model was designed to measure the amount of deflection of Steinmann pins of various diameters using a Kirschner tensioning bow, a Böhler (nontensioning) device, and a simple design using only weight and nylon cord. Increasing weight was added to each system and deflection recorded. Data were then evaluated to determine the smallest pin diameter that can reasonably withstand a weight of 35 pounds using the cord-only traction design. Results: Overall, larger pins deflected less. When comparing the traction systems, the tensioned bow had the least deflection, followed by the nontensioned bow, and the cord-only system. In the cord-only system, the 2.8-mm pin was the smallest diameter that successfully withstood the maximum weight without failing. The cord-only design was left in place for 48 hr without further increase in deflection. Conclusions: A simple skeletal traction design consisting of a 2.8-mm smooth Steinmann pin, segment of nylon cord, and weight can be applied with limited tools in a safe and efficient manner.